‘Some Are Good, Some Are Bad’: Perceptions of the Police from Black and Latina Women Living in the San Francisco Bay Area - Wilson, Ida (Women & criminal justice, 2021)
In recent years, high profile cases involving the deadly use of force on men and boys of color have raised concerns about police interactions with people of color. In general, these highly publicized cases have consolidated the view that men of color are the primary targets. While this focus is important, it has led, nevertheless, to an overshadowing of women of color’s experiences with police violence and their perceptions of the police. In order to begin to fill this gap, this paper, using in-depth interviews with 49 women of color residing in the San Francisco Bay Area, explores their perceptions of the police and the factors that influence their views. Analysis of the narrative data revealed that women do not view the police positively and suggests that personal and vicarious experiences with the police through friends, family members and the media operated as influential factors that shaped their perceptions of police.